PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PERTANIAN DI KELURAHAN KEDAUNG KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Simamora, Werna Newell; Zakaria, Wan Abbas; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purpose of this study was to analyze the main farming income, annual household income, welfare, and factors that influence the level of household welfare. Data were collected in June - August 2018. The research location was determined intentionally because the Kedaung Village was one of the regions with high poverty levels in the Kemiling District of Bandar Lampung City. The number of respondents in this study was 40 respondents taken using simple random sampling technique. The analytical methods used were farm income analysis, household income analysis, and welfare level analysis. The results of the study explained that the average main farming income was differentiated based on two cropping patterns, namely: first cropping pattern (beans - beans) amounting to Rp2,537,872.35 /0,08 ha per year, while in the second cropping pattern (beans - long beans) amounting to Rp2,830,339.88 /0,07ha per year. The average household income every year based on cropping patterns was Rp23,317,784.40 per year of the first cropping pattern and Rp13,841,450.10 per year of the second cropping pattern. As many as 95 percent of agricultural households in Kedaung Sub-District, Kemiling District, Bandar Lampung City are in the category of unprosperous. This situation occurs because of low social, educational, and health scores.Keywords: agriculture household, income, welfare indicators